Linking land value to indicators of soil quality and land use pressure - John J. Drewry; Stephen J. McNeill; Richard W. McDowell; Richard Law; Bryan A. Stevenson (Geoderma)
Soil quality is used to assess the soil’s ability to maintain ecological and environmental quality as well as agricultural productivity. A unique indicator associated with land use pressure is agricultural land value. Because land value is assessed at a property scale and regularly updated, we considered land value to be a good proxy for agricultural intensification. We therefore tested whether a relationship exists between land value per hectare, point-scale soil quality, other land pressure indicators (stock numbers, dominant land use), and catchment characteristics, as this has not been tested previously. We used soil quality from a national soil quality monitoring dataset, and land pressure indicators across 192 catchments (31% of land area) in New Zealand. We tested an array of models with the random forest model exhibiting the best goodness-of-fit metrics. The most important explanatory variable in predicting land valuation per hectare in the random forest model was catchment elevation (mean decrease in the mean square error; 0.92), followed by catchment potential evapotranspiration (0.78). Similarly, the fraction of dairy (0.28) and arable (0.27) land use had a relatively important effect, as did soil pH (0.32), the C:N ratio (0.31), and carbon concentration (0.30). We conclude that that land value per hectare has a well-defined relationship with land use and some soil quality measures, though expressing soil quality data at a catchment scale presented some challenges. Although the relationship was complicated, this study indicates that further work to determine if land value could act as an integrating proxy for land intensification is warranted.